2009
DOI: 10.1002/ppap.200930903
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Non‐equilibrium Atmospheric‐Pressure and Low‐Pressure Plasma Treatments of Poly(styrene–butadiene–styrene) Elastomers

Abstract: Low‐pressure plasma generated in a typical parallel plate reactor and atmospheric pressure plasma produced by a plasma needle were utilized to modify the surface of poly(styrene–butadiene–styrene) (SBS) elastomers. An RF discharge (13.56 MHz) in helium was used in the both cases. The SBS surfaces were investigated by T‐peel tests, contact‐angle measurements, and IRS–FTIR spectroscopy. It has been found that such plasma treatments drastically improve the strength of adhesive‐bonded joints between the SBS surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Bhowmik et al have revealed that higher incorporation of oxygen functionalities have been obtained, when polypropylene surface is exposed to DC glow discharge under stainless steel electrode fol lowed by nickel and copper electrodes as evident from XPS studies and these oxygen functionalities have been transformed into various polar functional groups and which has been attributed to increase in surface energy of the polymer leading to increase in adhesion [25]. Tyczkowski et al [26] have investigated low pres sure plasma generated in a typical parallel plate reactor and atmospheric pressure plasma produced by a plasma needle to modify the surface of poly(styrene butadiene styrene) (SBS) elastomers. It has been found that such plasma treatments drastically improve the strength of adhesive bonded joints between the SBS surfaces and polyurethane adhesives; however, the plasma needle operation under atmospheric pres sure plasma has turned out to be more effective.…”
Section: Effect Of Surface Energy On the Lap Shear Tensilementioning
confidence: 99%
“…Bhowmik et al have revealed that higher incorporation of oxygen functionalities have been obtained, when polypropylene surface is exposed to DC glow discharge under stainless steel electrode fol lowed by nickel and copper electrodes as evident from XPS studies and these oxygen functionalities have been transformed into various polar functional groups and which has been attributed to increase in surface energy of the polymer leading to increase in adhesion [25]. Tyczkowski et al [26] have investigated low pres sure plasma generated in a typical parallel plate reactor and atmospheric pressure plasma produced by a plasma needle to modify the surface of poly(styrene butadiene styrene) (SBS) elastomers. It has been found that such plasma treatments drastically improve the strength of adhesive bonded joints between the SBS surfaces and polyurethane adhesives; however, the plasma needle operation under atmospheric pres sure plasma has turned out to be more effective.…”
Section: Effect Of Surface Energy On the Lap Shear Tensilementioning
confidence: 99%
“…Radiation‐based treatments (corona discharge,6–8 ultraviolet,9, 10 low11–17 and atmospheric pressure or plasma torch18, 19 plasmas) for surface modification of rubber have been proved to be efficient to improve wettability and adhesion properties. In the case of plasma treatments, the gas nature, the time of treatment and the reactor configuration, among other, determine the extent of surface modification of polymers.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Tyczkowski et al [12] have investigated low-pressure plasma generated in a typical parallel plate reactor and atmospheric pressure plasma produced by a plasma needle to modify the surface of poly(styrene-butadiene-styrene) (SBS) elastomers. An RF discharge (13.56 MHz) in helium was used in the both cases.…”
Section: Discussionmentioning
confidence: 99%